Study on water loss settlement law of loose aquifer based on distributed optical fiber - Liangji XU; Zongyou CAO; Xiaopeng LIU; Kun ZHANG; Yongqi LIU (Meitan kexue jishu, 2023)
Indirect water loss caused by disturbance from coal mining can cause compression of loose layers and surface subsidence, which poses a threat to coal mine safety. To analyze the effects of such non-mining factors on water loss and subsidence of loose aquifers, the study area was divided into seven layers from top to bottom based on existing geological and hydrological data. Using distributed fiber optic monitoring technology, hydrological observation techniques, and soil mechanics experiments, the loose aquifer in the study area was comprehensively observed and the deformation characteristics of each layer under non-mining conditions were analyzed. The weakening law of the deep aquitard was explored, and the relationship between the deformation of the deep aquifer and the water head height of that layer was determined. The results show that: ① continuous compression of the fourth aquifer and its upper part of the aquitard is the main cause of surface subsidence in the study area. The two layers that contribute the most to the deformation of the strata are the fourth and first aquifers, with the latter showing seasonal deformation characteristics. The fourth aquifer exhibits a continuous subsidence trend during the observation period. ② By combining hydrological boreholes, distributed fiber optic and soil mechanics experiments, monitoring of the degree of clay weakening of the target layer was achieved. The clay layer above the fourth aquifer in the study area is weakened by the impact of the groundwater in the fourth aquifer. The degree of weakening is inversely proportional to the burial depth and directly proportional to the permeability of the groundwater, and the weakening of the clay layer will cause compression of the aquitard at the top of the aquifer and exacerbate surface subsidence. ③ The deformation of the fourth aquifer is consistent with the trend of changes in the water head of the fourth aquifer, and the two are linearly related. The observation results are in agreement with the theoretical calculation results, indicating that water loss from the fourth aquifer is the main cause of its compression deformation.